Conocimientos y actitudes de los médicos en dos áreas sanitarias sobre las voluntades vitales anticipadas - Simón-Lorda, Pablo (Aten Primaria, 2008)
OBJECTIVES: To explore the knowledge and attitudes of physicians towards advance directives in two healthcare areas.To compare the outcomes of both areas.To compare the outcomes of primary healthcare and specialised healthcare. DESIGN: A cross sectional, descriptive study by means of a self-administered questionnaire. SETTING: North-Málaga and North-Almería healthcare areas, Spain. PARTICIPANTS: Physicians of primary and specialised healthcare. MEASUREMENTS AND MAIN RESULTS: Knowledge and attitudes towards advance directives. 194 (63.19%) questionnaires were filled out by the physicians from both healthcare districts. Mean age (standard deviation) 42.54 (80.85); 65.5% of participants were men and 33.5% were women; 51.55% from primary care and 48.45% from specialised healthcare. CONCLUSIONS: Polled physicians revealed a positive attitude towards the usefulness of advance directives for the patient's relatives and for healthcare professionals. They also show a positive attitude towards the use and respect of advance directives. They show a high predisposition to registry their advance directive, but a low predisposition to do so in a short term.